Applications of the Moore-Penrose Inverse in Digital Image Restoration. (13th October 2009) - Chountasis, Spiros; Katsikis, Vasilios N.; Pappas, Dimitrios
Abstract : This paper presents a fast computational method that finds application in a broad scientific field such as digital image restoration. The proposed method provides a new approach to the problem of image reconstruction by using the Moore-Penrose inverse. The resolution of the reconstructed image remains at a very high level but the main advantage of the method was found on the computational load that has been decreased considerably compared to the classic techniques.